2006
DOI: 10.1038/sj.emboj.7601473
|View full text |Cite
|
Sign up to set email alerts
|

Autoproteolysis of PIDD marks the bifurcation between pro-death caspase-2 and pro-survival NF-κB pathway

Abstract: Upon DNA damage, a complex called the PIDDosome is formed and either signals NF-jB activation and thus cell survival or alternatively triggers caspase-2 activation and apoptosis. PIDD (p53-induced protein with a death domain) is constitutively processed giving rise to a 48-kDa N-terminal fragment containing the leucine-rich repeats (LRRs, PIDD-N) and a 51-kDa C-terminal fragment containing the death domain (DD, PIDD-C). The latter undergoes further cleavage resulting in a 37-kDa fragment (PIDD-CC). Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
222
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(241 citation statements)
references
References 35 publications
(65 reference statements)
17
222
2
Order By: Relevance
“…We have recently shown that PIDD isoform 1 is autoprocessed at S446 and S588 to generate a PIDD-C and a PIDD-CC fragment (Tinel et al, 2007), in agreement with previous reports (Telliez et al, 2000;Pick et al, 2006). The 11 amino-acid deletion in isoform 2 encompasses the second cleavage site used for PIDD The two C terminal fragments generated by PIDD autoprocessing have distinct functions (Tinel et al, 2007).…”
Section: Pidd Isoforms 1 2 and 3 Activate Nf-kbsupporting
confidence: 90%
See 2 more Smart Citations
“…We have recently shown that PIDD isoform 1 is autoprocessed at S446 and S588 to generate a PIDD-C and a PIDD-CC fragment (Tinel et al, 2007), in agreement with previous reports (Telliez et al, 2000;Pick et al, 2006). The 11 amino-acid deletion in isoform 2 encompasses the second cleavage site used for PIDD The two C terminal fragments generated by PIDD autoprocessing have distinct functions (Tinel et al, 2007).…”
Section: Pidd Isoforms 1 2 and 3 Activate Nf-kbsupporting
confidence: 90%
“…Two levels of regulation had already been reported: at the transcriptional level, as PIDD is a known p53 target gene , and at the post-translational level, as autoprocessing of PIDD determines its partners of interaction and, therefore, the downstream signaling events (Tinel et al, 2007). The alternative splicing of PIDD that we report here could represent a third level of regulation, acting at the post-transcriptional level.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…21 Cleavage at an HFS site is also involved in the biogenesis of the nuclear envelope protein Nup98. 22 Surprisingly, by sequence comparison, we identified a bona fide HFS site in Unc5CL (aa 227-229) but not in any other ZU5-UPA-DDcontaining proteins, suggesting that Unc5CL might also undergo such autoproteolytic cleavage (Figures 1a and b and Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on Nup98 and PIDD have shown that this site can be cleaved involving formation of a thioester intermediate via an N-S acyl shift. 21,22 However, cleavage of the thioester intermediate requires addition of the nucleophilic agent hydroxylamine. To test whether Unc5CL HFC also forms a thioester intermediate, we analyzed the sensitivity to hydroxylamine-induced cleavage ( Figure 1e).…”
Section: Resultsmentioning
confidence: 99%